KONTRIBUSI KOPERASI PADA PENINGKATAN FINANCIAL LITERACY SEKOLAH DASAR DI KECAMATAN TUREN KABUPATEN MALANG - Anugerah, Roy; Hidayat, Aviessena Syaiful (Manajemen & Bisnis Jurnal, 2018)
The existence of elementary schools in Turen Sub-district was a part of the Indicator that there were stakeholders who have a mission to improve human resources and eventually there would emerge various generations of the nation who have extensive knowledge and dedicated to advancing the Indonesian Nation. On the other hand, the establishment of these schools was inseparable from economic activities, where many students gather with various needs that they have and guardians of students, of course, so this was a great opportunity for the creation of economic transactions in the school environment. The purpose of this study were: 1) To find out whether the establishment of cooperatives in the elementary school environment provides financial benefits or not. 2) To find out whether the establishment of cooperatives in the elementary school environment contributes to the school's financial literacy capabilities. This study used descriptive qualitative methods with the intention to understand the phenomena about what was experienced by research subjects by utilizing various natural methods. The results of this study indicated that: 1) Cooperatives have an important role to play in the financial / school financial contributions. 2) The Role of School Cooperatives towards Financial Literacy about a) Knowledge and skills in the form of Tawasi and Tasula Activities are activities that indirectly provide students and guardians with skills regarding finance (finance), about the importance of measuring financial ability and financial management ability itself, b) About basic financial management, such as saving behavior and financial participation. Savings activities give students an understanding of the importance of managing finances themselves. This activity will be felt when they has been in class 6 , and saw the results of their savings. c) about how someone behaves and responsible for money. That the Mandatory Savings and Voluntary Savings activities provide learning to students specifically how they treat pocket money given by parents, the responsibility given to the money. Keyword: School Coperation, and Financial Literacy